Experimental and Theoretical Dielectric Studies of PVDF/PZT Nanocomposite Thin Films - Zak, A.K.; Gan, W.C.; Abd Majid, Wan Haliza; Darroudi, M.; Velayutham, T.S. (2011)
Poly(vinylidene fluoride)/lead zirconate titanate nanocomposite thin films (PVDF/PZT-NPs) were successfully prepared by mixing fine Pb(Zr(0.52),Ti(0.48))O(3) nanoparticles (PZT-NPs) into a PVDF solution under ultrasonication. The mixture was spin coated onto glass substrate and then cured at 110 degrees C. X-ray diffraction (XRD), transmission electron microscopy (TEM), and scanning electron microscopy (SEM) were used to characterize the structure and properties of the obtained thin-film nanocomposites. The dielectric properties of the PVDF/PZT-NPs were analyzed in detail with respect to frequency. In comparison with pure poly (vinylidene fluoride), the dielectric constant of the nanocomposite (15 vol. PZT-NPs) was significantly increased, whereas the loss tangent was unchanged in the frequency range of 100 Hz to 30 MHz. The nanocomposites exhibited good dielectric stability over a wide frequency range. Different theoretical approaches were employed to predict the effective dielectric constants of the thin film nanocomposite systems, and the estimated results were compared with the experimental data. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.